Cytotoxicity Enhancement of α-Mangostin with Folate-Conjugated Chitosan Nanoparticles in MCF-7 Breast Cancer Cells - Yedi Herdiana; Nasrul Wathoni; Shaharum Shamsuddin; Muchtaridi Muchtaridi (Molecules, 2023)
α-mangostin (AM) is a promising natural anticancer agent that can be used in cancer research. However, its effectiveness can be limited by poor solubility and bioavailability. To address this issue, chitosan-based nanoparticles (CSNPs) have been investigated as a potential delivery system to enhance the cytotoxicity to cancer cells and improve selectivity against normal cells. In this study, we developed folate-conjugated chitosan nanoparticles (F-CS-NPs) using a carbodiimide-based conjugation method to attach folate to chitosan (CS), which have different molecular weights. The NPs were crosslinked using tripolyphosphate (TPP) via ionic gelation. To characterize the F-CS-NPs, we utilized various analytical techniques, including transmission electron microscopy (TEM) to evaluate the particle size and morphology, Fourier-transform infrared spectroscopy (FTIR) to confirm the presence of functional groups, and ultraviolet-visible spectroscopy (UV-Vis) to measure the absorption spectrum and confirm the presence of folate. The particle size of AM-F-CS-NPs ranged from 180 nm to 250 nm, with many having favorable charges ranging from +40.33 ± 3.4 to 10.69 ± 1.3 mV. All NPs exhibited the same spherical morphology. The use of F-CS-NPs increased drug release, followed by a sustained release pattern. We evaluated the cytotoxicity of AM, AM-F-CS-HMW, and AM-F-CS-LMW NPs against MCF-7 cells and found IC50 values of 8.47 ± 0.49, 5.3 ± 0.01, and 4.70 ± 0.11 µg/mL, respectively. These results confirm the improved cytotoxicity of AM in MCF-7 cells when delivered via F-CS-NPs. Overall, our in vitro study demonstrated that the properties of F-CS-NPs greatly influence the cytotoxicity of AM in MCF-7 breast cancer cells (significantly different (p < 0.05)). The use of F-CS-NPs as a drug-delivery system for AM may have the potential to develop novel therapies for breast cancer.